(untitled) (REMUNOM, 2025)
Abstract The replacement of foods considered healthy by industrialized foods rich in additives contributes to the configuration of the current dietary profile of the Brazilian population, characterizing a greater consumption of ultra-processed foods, which becomes a determining factor for Chronic Non-Communicable Diseases and has as its main consequence the premature insertion of these foods into children’s diets. Objective: To analyze the early introduction of industrialized foods in the formation of children’s eating habits in early childhood. Methodology: This is an integrative review study, with papers published in the last decade (2015 to 2025), found in the following databases: Scielo, Pubmed and Scopus, in English and Portuguese, totaling a final sample of 19 original articles. Results: Factors associated with the consumption of ultra-processed foods in early childhood were found to be highly prevalent among children under two years old. Maternal schooling, income and socioeconomic conditions were found to have a positive impact on the consumption of these foods, to the detriment of foods considered healthy. Children who are not breastfed or who are exclusively breastfed for less than 180 days are at increased risk of introducing four or more ultra-processed foods in the first year of life. intervention to promote healthy eating habits from the first years of life. Conclusion: This study provided a better understanding of the consumption of ultra-processed foods in children, with an emphasis on early childhood.